Platelet rich concentrate enhances mesenchymal stem cells capacity to repair focal cartilage injury in rabbits. Issue 4 (April 2018) - Samuel, Shani; Ahmad, Raja Elina; Ramasamy, Thamil Selvee; Manan, Faizal; Kamarul, Tunku
Abstract: Background: It has been previously suggested that the use of regenerative promoters, which include bone marrow-derived mesenchymal stem cells (MSCs) or natural growth factors supplement such as platelet-rich concentrate (PRC) could promote cartilage regeneration. However, the notion that the concurrent use of both promoters may provide a synergistic effect that improves the repair outcome of focal cartilage injury has not been previously demonstrated. This study was thus conducted to determine whether the concomitant use of PRC could further enhance the reparative potential of MSCs encapsulated in alginate transplanted into focal cartilage injury in rabbits. Methods: Artifically created full thickness cartilage defects were made on the weight-bearing region of medial femoral condyles in bilateral knees of New Zealand White rabbits (N = 30). After one month, the right knee was treated with either i) PRC (n = 10), ii) MSCs (n = 10), or, iii) a combination of PRC and MSCs (PRC + MSC) (n = 10), all encapsulated in alginate. The left knee remained untreated (control). Rabbits were sacrificed at 3 and 6 months after treatment. Cartilage tissue regeneration was accessed using ICRS morphologic scoring, histologic grading by O'Driscoll scoring, immunohistochemical staining and quantitative analysis of glycosaminoglycans (GAG) per total protein content. Results: At 3 months, transplantation using PRC alone was equally effective as MSCs in inducing the repair of cartilage defects. However, PRC + MSC resulted in significantly higher ICRS and O'Driscoll scores ( p <  0.05) as compared to other groups. The regenerated tissues from the PRC + MSC group also had stronger staining for Safranin-O and collagen type II. By 6 months, in addition to superior ICRS and O'Driscoll scores as well as stronger staining, glycosaminoglycan per total protein content was also significantly higher (p < 0.05) in the PRC + MSC group (3.4 ± 0.3 μg/mg) as compared to the MSC (2.6 ± 0.2 μg/mg) or PRC (2.1 ± 0.2 μg/mg) groups. Conclusion: PRC enhances the reparative effects of MSC in treating focal articular cartilage injuries.